2003
DOI: 10.1046/j.1523-1755.2003.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of TGF-β action ameliorates renal dysfunction and histologic progression in anti-GBM nephritis

Abstract: This study demonstrated for the first time that the blockade of TGF-beta action by AdTbeta-ExR in the early stage of anti-GBM nephritis ameliorates the clinical and histologic progression. In addition, this study shed light on the development of a specific gene therapy for human crescentic glomerulonephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 32 publications
(4 reference statements)
1
33
2
Order By: Relevance
“…The present study has answered all these questions by adenovirus-mediated expression of a soluble TGF-b receptor that can abolish TGF-b signaling. [14][15][16] It is now recognized that repeated episodes of acute pancreatitis can lead to increasing residual damage to the gland, eventually resulting in chronic pancreatitis (the necrosis-fibrosis sequence). 17,34,35 Therefore, we chose this chronic pancreatitis model induced by repeated acute pancreatitis in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study has answered all these questions by adenovirus-mediated expression of a soluble TGF-b receptor that can abolish TGF-b signaling. [14][15][16] It is now recognized that repeated episodes of acute pancreatitis can lead to increasing residual damage to the gland, eventually resulting in chronic pancreatitis (the necrosis-fibrosis sequence). 17,34,35 Therefore, we chose this chronic pancreatitis model induced by repeated acute pancreatitis in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we showed that serum level of this soluble receptor reached a peak value at 5-7 days after the injection and gradually declined thereafter, but that it was still detectable even at 21 days after injection. [14][15][16] Animals Male BALB/c mice (Kyudo Co., Kumamoto, Japan) weighing 20-22 g were used. The animals were kept in a 12 h light/dark cycle with free access to water and a standard mouse chow.…”
Section: Replication-defective Recombinant Adenovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, suppression of TGF-␤ signaling has been included in several therapeutic approaches for preventing renal fibrosis. 10,11 PAI-1 is the main physiologic inhibitor of the tissue and urokinase plasminogen activator and is considered to be the most important inhibitor of fibrinolysis. 12 However, plasminogen inhibition does not explain the action of PAI-1 in renal fibrosis.…”
mentioning
confidence: 99%
“…These drugs have proven useful in experimental rapidly progressive GN, where they inhibited the formation of crescents [61][62][63][64][65][66][67], and in mouse strains having developed spontaneously SLE [68].…”
Section: Anti -Tnfmentioning
confidence: 99%